PERBANDINGAN DIALEK IBARAKI DENGAN RAGAM STANDAR BAHASA JEPANG - Ghea Rizky Ananda; Arza Aibonotika; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Dialect is one of language variations. Japan is the one of many countries in the world that has many variations of dialects. One of them is Ibaraki dialect. Ibaraki is a prefecture of Japan located in Kanto region near Tokyo with Mito as The Capital city. Ibaraki dialect is not really well-known like The Osaka dialect or Kyoto dialect but it is exist. Ibaraki's native speaker is more known as Ibarakian, but not all Ibarakian is speaking the dialect. The Ibaraki dialect's structure is not really complicated and does not has so many variations but it has a special pronounciation that makes it well-recognised. There are three problems to be solved for the study, namely: (1) How is the comparison of Ibaraki dialect with The Standard Japanese phonologically, (2) morphologically and (3) lexically. This study is using quantitative description. The data source is a textbook whose title is Gojappedia Tanoshiku Manabu Ibaraki Ben and a couple of native speakers which happened to be lecturers in one of the Ibaraki Prefecture's University located in Hitachi, the Ibaraki Christian University. The results will be collected, tabulated, classified, then analyzed. As the results, there are 72 datas in total of the comparison, there are 7 datas in morphology, 38 datas of phonology, and 26 datas of lexical.Key Words: Ibaraki dialect, The Standard Japanese, Morphology, Phonology, Lexical